Analisis Strategi Mutu Pendidikan Nasional: Perspektif Total Quality Management Dalam Sistem Pendidikan Agama Islam - Ahmad Izzuddin Faqih; Khoirul Anwar; Mu'alimin (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze Indonesia's national education quality strategy for the 2020-2025 period and the implementation of Total Quality Management (TQM) in the context of Islamic Religious Education (IRE/PAI). Using a Systematic Literature Review (SLR) with the PRISMA 2020 protocol on 53 documents (15 government policies and 38 reputable journal articles from Scopus Q1-Q2 and SINTA 1-2, period 2020-2026), and thematic content analysis with NVivo 14 (source triangulation validity; inter-coder reliability Cohen's Kappa=0.85), the study identifies five critical gaps between macro-policy and micro-implementation: conceptual gaps between quantitative standardization and qualitative character formation, capacity gaps where 77% of madrasahs do not effectively use the Education Report Card, resource gaps with a 1:4 disparity between Java and Papua, accountability gaps causing accreditation fatigue, and temporal gaps due to rapid policy changes. The study produces an Islamic-TQM Framework integrating the values of itqan, ihsan, amanah, and istiqamah with classical TQM principles as a contextual solution. Recommendations include strengthening SPMI through a tiered approach, Communities of Practice for intensive mentoring, reorientation of evaluation from compliance to development, transformation of quality culture based on Islamic values, and affirmative policies for equitable quality across regions.